Jeremy Thatcher, dragon hatcher - Coville, Bruce; Lippincott, Gary A. (San Diego : Jane Yolen Books, 1991)
Small for his age but artistically talented, twelve-year-old Jeremy Thatcher unknowingly buys a dragon's egg.
"A magic shop book."
Keywords: Dragons -- Fiction; Friendship -- Fiction; Pets -- Fiction; Drawing -- Fiction; Size -- Fiction